Geothermal energy systems - Dinçer, İbrahim, 1964-; Öztürk, Murat (Researcher in clean energy) (Elsevier, 2021)
An analysis of conceptual approaches to geothermal energy systems for different applications, with fundamentals related to the geothermal energy sources, systems, and components.
Includes index.
Keywords: Geothermal power plants.; Geothermal resources.; elektronické knihy; electronic books